Kinetics of luminol sonochemiluminescence quenched by purines. (19th June 2012) - Wang, Jian; Lai, Yongquan; Chen, Meili; Jiang, Zhou; Chen, Guonan
ABSTRACT: A homogeneous chemiluminescence (CL) reaction was initiated by ultrasound irradiation. Luminol sonochemiluminescence (SCL) reaction kinetics were determined under pseudo‐first‐order conditions, and the reaction followed the model for simple rise–fall kinetics. In addition, SCL quenching reactions induced by purines were also investigated in which the interactions between luminol and purines were analysed using the Stern–Volmer (S‐V) mechanism. The results implied that the high rate constant of luminol CL quenched by purines may be attributed to ground state interactions originating from hydrogen bonding. Copyright © 2012 John Wiley & Sons, Ltd.